Cucumis Metuliferus Fruit Extract Loaded Acetate Cellulose Coatings for Antioxidant Active Packaging - Guarda-Moraga, A; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A; Riveros-Faba, S; Garrido-Ayala, L (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
A new active coating was developed by using Cucumis metuliferus fruit extract as antioxidant additive with the aim of obtaining an easy way to functionalize low-density polyethylene (LDPE) films for food packaging applications. Thus, an extraction protocol was first optimized to determine the total phenolic compounds and the antioxidant activity of CM. The aqueous CM antioxidant extract was then incorporated into cellulose acetate (CA) film-forming solution in different concentrations (1, 3 and 5 wt.%) to be further coated in corona-treated LDPE to obtain LDPE/CA-CM bilayer systems. CA and CA-CM film-forming solutions were successfully coated onto the surface of LDPE, showing good adhesion in the final bilayer structure. The optical, microstructural, thermal, mechanical and oxygen barrier performance, as well as the antioxidant activity, were evaluated. The active coating casted onto the LDPE film did not affect the high transparency of LDPE and improved the oxygen barrier performance. The antioxidant effectiveness of bilayer packaging was confirmed by release studies of Cucumis metuliferus from the cellulose acetate layer to a fatty food simulant. Finally, the LDPE/CA-CM active materials were also tested for their application in minimally processed fruits, and they demonstrated their ability to reduce the oxidation process of fresh cut apples. Thus, the obtained results suggest that CA-CM-based coating can be used to easily introduce active functionality to typically used LDPE at industrial level and enhance its oxygen barrier, without affecting the high transparency, revealing their potential application in the active food packaging sector to extend the shelf-life of packaged food by prevention of lipid oxidation of fatty food or by prevention fruit browning. © 2020 by the authors.